The need for the formation of higher education students’ political culture: the challenges of today - Posohov, V.; Kuruch, A. (Problems of Engineer-Pedagogical Education, 2021)
The article considers the conditions of forming political culture of students at higher educational institutions of Ukraine. The difficulties connected with the formation of a developed, consolidated democracy in Ukraine and explained by the insufficiently high level of political culture are considered. The causes for the socio-political crisis in Ukraine are analyzed in detail, they are the lack of national unity, political confrontation based on ideological and socio-economic differences; crisis of power, based on the inconsistency of the political system with the real conditions of its application; lack of legal culture and legal nihilism of its citizens; ethno-national and social problems in society. The main historical events that have influenced the formation of statehood and political views of Ukrainians are described. The article considers the national mentality and features of its formation on the territory of Eastern and Southern Ukraine. The consequences of forming such a worldview are analyzed and it is noted that Ukrainians see the future of the country differently. It is concluded that most political forces in Ukraine are not trying to create a common vision of the future of Ukraine and that a significant number of political movements are not interested in the unification of Ukraine as, on the contrary, they manipulate the consciousness of citizens and support the schism under various political slogans and myths. Such manipulative actions are only possible if citizens’ political culture is not well-rounded. It is emphasized that most countries followed the same path during their formation. The necessity of forming political culture of young people at higher education institutions is substantiated, because they are the future economic and intellectual potential of the state. It is concluded that in modern conditions, in order to ensure political stability in Ukraine, it is necessary to focus on the formation of political culture among students while they are getting higher education, thus including young people in the political life of the country. A well-developed political culture will allow understanding the world political process, and will promote creation of a civil society